Government And Taxpayers Interests' Coordination Model Within The CGT, Based On The Principle Of Social And Economic Efficiency; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Bannova K. A. Kristina Alekseevna; Dolgikh I. N. Irina Nikolaevna; Pokrovskaia N. V. Nataljya Vladimirovna; Kropova A. A. Alyona Anatoljevna (2016, 2016)
Title screen